(untitled) (Journal of Advanced Veterinary and Animal Research, 2026)
Objective: To assess benzalkonium chloride (BAC) contamination in abattoir wastewater and evaluate disinfectant usage practices in Western Thailand. Materials and Methods: Wastewater samples and questionnaire data were collected from 20 pig and poultry abattoirs. BAC analogues were detected using ultra-high-performance liquid chromatography with diode array detection. Associations between abattoir scale and safety practices were analyzed using Fisher’s exact test, with effect sizes expressed as Cramer’s V. Results: BAC residues were identified in all abattoirs, including 40% that reported not using BACbased disinfectants. Four large-scale facilities discharged wastewater into public waterways, posing environmental risks. Significant associations were found between abattoir scale and safety measures: safety training (Cramer’s V = 0.59), personal protective equipment availability (0.57), and spill kit preparedness (0.89). Large-scale facilities adhered to these measures, while small and medium operations showed limited compliance. Although smaller facilities did not discharge into public areas, insufficient safety practices may contribute to BAC accumulation. Conclusion: BAC residues are widespread in abattoir wastewater. Strengthened regulatory oversight, systematic monitoring, and routine safety training are essential to mitigate environmental and occupational hazards. J. Adv. Vet. Anim. Res., 12(4): 1108–1114, December 2025 http://doi.org/10.5455/javar.2025.l971